Emergency Response in Healthcare: Areas That Need Significant Intervention In Sub-Saharan Africa (SSA) - Achieng’, Loice A.; Agola, Joshua; Liyala, Samuel (International Journal of Innovative Research and Advanced Studies (IJIRAS), 2022)
Emergency health response is one of the most important healthcare services as it is the last line of defense against mortality from accidents or chronic conditions. Nonetheless, the COVID-19 pandemic highlighted numerous issues and concerns about the current emergency response, its limitation, and what needs to be done. Considering the importance of emergency response in healthcare, the current study evaluated the areas that need immediate intervention with respect to emergency health services in sub-Saharan Africa. The current study was qualitative and adopted a systematic literature review approach. The study reviewed articles from reputable journals published between 2012-2022. the researcher identified 170 articles. However, after vigorous evaluation of the quality of the journals, only 10 met the inclusion criterion. Conclusions: the review highlighted a myriad of issues in the emergency health response in Sub-Saharan Africa. These include poor supply chain and logistics, poor infrastructure, inadequate medical facilities, limited resources, lack of coordinated emergency service provision, overcrowding of the emergency department, and limited bed capacity.
Keywords: Emergency; Sub-Saharan Africa; Medical Facilities; Healthcare